2014
DOI: 10.5455/medscience.2014.03.8160
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between ABO Blood Group and Glioblastoma Multiforme

Abstract: Glioblastoma Multiforme (GBM) is the most common type of primary brain tumor and its prognosis is poor. Some studies have investigated the relationship between ABO Blood

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“… 7 Previously, many different results have been reported in other cancer types. 8 The association of ABO blood groups with diabetes mellitus has been observed earlier in several epidemiological and genetic studies and resulted with inconsistent findings. 7 No association has been observed between essential HT and ABO blood groups in a study, while another study showed that the blood group B was seen more in the HT and obesity.…”
Section: Introductionmentioning
confidence: 99%
“… 7 Previously, many different results have been reported in other cancer types. 8 The association of ABO blood groups with diabetes mellitus has been observed earlier in several epidemiological and genetic studies and resulted with inconsistent findings. 7 No association has been observed between essential HT and ABO blood groups in a study, while another study showed that the blood group B was seen more in the HT and obesity.…”
Section: Introductionmentioning
confidence: 99%
“…On the contrary, in a case-control study, Akca et al, aimed to compare the patients with glioblastoma multiforme with control groups regarding ABO blood groups. On the basis of the study results, no significant differences among O, A, B and AB blood groups were shown [24]. In a study conducted by Turowski and Czochra, the analysis was based on the distribution of ABO blood groups in 271 patients treated for glioblastoma multiforme (GBM), whereas the control group included 500 patents with craniocerebral trauma.…”
Section: The Influence Of Abo Blood Group On the Development Of Gliomamentioning
confidence: 98%
“…Furthermore, several studies have shown conflicting results concerning the relationship between ABO blood groups and glioma risk [16][17][18][19][20][21][22][23][24][25][26][27][28][29]. Finally, differences are observed not only in the distribution of ABO blood group antigens among patients with primary brain tumors in various countries worldwide, but also among different ethnic groups within the country.…”
Section: Introductionmentioning
confidence: 99%
“…In glioblastoma multiforme, one study found no association, whereas another revealed an independent poor prognostic value for non-O blood groups. 26,27 Due to inconsistency and lack of any study over ABO blood groups effect over pediatric brain tumors, our current study aims to investigate the relationship between ABO blood groups and brain tumor incidence in the Jordanian pediatric population in a casecontrolled manner.…”
Section: Introductionmentioning
confidence: 99%